Pengaruh Sustainability Reporting terhadap Nilai Perusahaan dengan Intellectual Capital Sebagai Variabel Moderasi - Fitri Arinda Rahmawati; Suwarno Suwarno (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
This study aims to analyse the effect of sustainability reporting on company value with intellectual capital as a moderating variable in the Indonesian banking sector for the period 2020–2024. The sample consisted of 75 data selected through purposive sampling. The analysis technique utilises the Partial Least Squares Structural Equation Modelling approach through SmartPLS software. The results show that sustainability reporting has a significant negative effect on company value; intellectual capital also has a significant negative effect on company value; and the interaction between sustainability reporting and intellectual capital has a significant positive effect. These findings indicate that intellectual capital can strengthen the relationship between sustainability reporting and company value. These results can be explained through signalling theory, where sustainability information disclosure and intellectual capital function as signals to investors, but may be misinterpreted if not accompanied by adequate internal capabilities. Additionally, agency theory helps explain the potential conflict of interest between managers and shareholders that may influence perceptions of company value regarding sustainability reporting practices.